2008
DOI: 10.1097/mao.0b013e318184f492
|View full text |Cite
|
Sign up to set email alerts
|

Role of Electrode Placement as a Contributor to Variability in Cochlear Implant Outcomes

Abstract: Hypothesis Suboptimal cochlear implant (CI) electrode array placement may reduce presentation of coded information to the central nervous system and consequently limit speech recognition. Background Generally, mean speech reception scores for CI recipients are similar across different CI systems, yet large outcome variation is observed among recipients implanted with the same device. These observations suggest significant recipient-dependent factors influence speech reception performance. This study examines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
434
6
17

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 472 publications
(481 citation statements)
references
References 66 publications
15
434
6
17
Order By: Relevance
“…The classical implantation procedure involves drilling a path through the mastoid in order to reach the tympanic cavity allowing the surgeon to open the scala tympani (one of the three cochlear ducts) and insert an electrode array. The functional outcomes for these subjects are linked to the potential insertion traumas (Aschendorff et al, 2007;Finley et al, 2008). The insertion can lead to lesions of the modiolus, osseous spiral lamina or basilar membrane, resulting in degeneration of the ciliated (Adunka et al, 2004) and spiral ganglion cells (Leake et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The classical implantation procedure involves drilling a path through the mastoid in order to reach the tympanic cavity allowing the surgeon to open the scala tympani (one of the three cochlear ducts) and insert an electrode array. The functional outcomes for these subjects are linked to the potential insertion traumas (Aschendorff et al, 2007;Finley et al, 2008). The insertion can lead to lesions of the modiolus, osseous spiral lamina or basilar membrane, resulting in degeneration of the ciliated (Adunka et al, 2004) and spiral ganglion cells (Leake et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of imaging techniques, recent studies have shown that this event of displacement of the electrode array from the tympanic to the vestibular ramp is more frequent than thought and may be a reason for less favorable auditory performance in several patients. The cochleae do not all have the same shape and dimension whereby the (3) electrode array chosen for an implanted patient should be considered in an individualized manner [10,11,12].…”
Section: Resultsmentioning
confidence: 99%
“…1 It is important to be able to describe the CI tip location because electrode-array insertion depth and location are relevant factors when considering hearing and speech outcomes following CI insertion. [1][2][3][4] Audiologic outcomes are better when the electrode array is inserted into the scala tympani, allowing better stimulation of the spiral ganglion neural elements. Multidetector CT can detect the scala tympani in cadaveric specimens, 5 but application to routine clinical postimplantation imaging is limited.…”
mentioning
confidence: 99%